Pengaruh Penyimpanan dan Lama Pemanasan Terhadap Kadar Asam Galat pada Kacang Tanah (Arachis hypogaea L.): Effect of Storage and Heating Time on Gallic Acid Levels in Peanuts (Arachis hypogaea L.) - Devyana Dyah Wulandari; Ersalina Nidianti; Ary Andini; Rahmawati Fitri Awalia; Halimah Prisilia (KOVALEN: Jurnal Riset Kimia, 2022)
One of the most prevalent phenolic acids to be found in foods such as fruits, vegetables, and herbal remedies is gallic acid, also known as 3,4,5-trihydroxybenzoic acid. The free acids, esters, catechin derivatives, and hydrolyzed tannins are the different ways that these substances are obtained. The specialty of this compound is due to its pharmacological activity as a radical scavenger. The total phenolic content in peanuts varies from 132.5 to 248.8 mg GAE/100 g. The purpose of this study was to determine the effect of storage time and heating time of peanuts (Arachis hypogaea L.) on gallic acid levels. Determination of gallic acid using the High Performance Liquid Chromatography (HPLC) method with the column used is an ODS (Octadesil Silica) C18 column and the mobile phase is a mixture of acetonitrile and aquadest (1:3). Peanuts were stored for 1 week, 2 weeks, and 3 weeks at 25°C and fried at 160°C for 2 minutes, 4 minutes, and 6 minutes. The results of this study on the length of storage obtained a P value of 0.000 where the results are smaller than 0.05. This indicates that storage time has a significant effect on gallic acid levels in peanut samples. Gallic acid levels appear to increase from the first week to the fourth week. Based on the results of the research at the time of heating obtained a P value of 0.189 where the results are higher than 0.05. This shows that the length of heating time does not affect on the gallic acid content in the peanut samples. From these results, it was concluded that gallic acid content was affected by storage time, but not by heating time.